2020
DOI: 10.26434/chemrxiv.12477776.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Under Pressure: Mechanochemical Effects on Structure and Ion Conduction in the Sodium-Ion Solid Electrolyte Na3PS4

Abstract: <div> <p>Fast-ion conductors are critical to the development of solid-state batteries. The effects of mechanochemical synthesis that lead to increased ionic conductivity in an archetypical sodium-ion conductor Na<sub>3</sub>PS<sub>4</sub> are not fully understood. We present here a comprehensive analysis based on diffraction (Bragg, pair distribution function), spectroscopy (impedance, Raman, NMR, INS) and <i>ab-initio</i> simulations aimed at elucidating the sy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…At higher wavelengths, the peak of asymmetric stretch can be observed at 535 cm –1 ( ν 3 ). [ 8,20,42 ] Overall, in terms of bulk properties of the powders, it can be concluded that there is no evident difference between the four batches besides their average crystallite size.…”
Section: Resultsmentioning
confidence: 93%
“…At higher wavelengths, the peak of asymmetric stretch can be observed at 535 cm –1 ( ν 3 ). [ 8,20,42 ] Overall, in terms of bulk properties of the powders, it can be concluded that there is no evident difference between the four batches besides their average crystallite size.…”
Section: Resultsmentioning
confidence: 93%
“…Indeed, considering these anions as rigid spheres, their radius in each cubic sublattice is calculated according to the respective lattice parameter a, i.e., for fcc anion sublattice, R 2 by Famprikis et al, high-energy ball-milling provides mechanical stress that can stabilize a cubic polymorph of Na 3 PS 4 , which is denser with respect to the thermodynamic tetragonal one. 77 Nonetheless, in the case of MM-NCB, the stabilization of a bcc anion sublattice results in a structure with a less-efficient anion packing, with respect to the pseudo-fcc for the orthorhombic, pristine, NCB, thus allowing ∼15.7% more volume for the cation to move (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…72 This observation can be generalized to other solid electrolyte systems. Famprikis et al 73 recently summarized the activation volume, the change of activation barrier to pressure, for cation conduction in many solid electrolytes. Depending on the diffusion carrier (vacancy or interstitial), the activation volume is either positive or negative.…”
Section: Evaluation Of the Impact Of Stress On LI Diffusionmentioning
confidence: 99%